Accumulation of Phenolic Compounds and Expression Profiles of Phenolic Acid Biosynthesis-Related Genes in Developing Grains of White, Purple, and Red Wheat - Ma, Dongyun; Li, Yaoguang; Zhang, Jian; Wang, Chenyang; Qin, Haixia; Ding, Huina; Xie, Yingxin; Guo, Tiancai (Frontiers in Plant Science, 2016)
Polyphenols in whole grain wheat have potential health benefits, but little is known about the expression patterns of phenolic acid biosynthesis genes and the accumulation of phenolic acid compounds in different-colored wheat grains. We found that purple wheat varieties had the highest total phenolic content (TPC) and antioxidant activity. Among phenolic acid compounds, bound ferulic acid, vanillic, and caffeic acid levels were significantly higher in purple wheat than in white and red wheat, while total soluble phenolic acid, soluble ferulic acid, and vanillic acid levels were significantly higher in purple and red wheat than in white wheat. Ferulic acid and syringic acid levels peaked at 14 days after anthesis (DAA), whereas p-coumaric acid and caffeic acid levels peaked at 7 DAA, and vanillic acid levels gradually increased during grain filling and peaked near ripeness (35 DAA). Nine phenolic acid biosynthesis pathway genes (TaPAL1, TaPAL2, TaC3H1, TaC3H2, TaC4H, Ta4CL1, Ta4CL2, TaCOMT1, and TaCOMT2) exhibited three distinct expression patterns during grain filling, which may be related to the different phenolic acids levels. White wheat had higher phenolic acid contents and relatively high gene expression at the early stage, while purple wheat had the highest phenolic acid contents and gene expression levels at later stages. These results suggest that the expression of phenolic acid biosynthesis genes may be closely related to phenolic acids accumulation.